The reconstruction of the Mekhilta of Rabbi Shimon b. Yohai. A reexamination - Nelson, David W. (Hebrew Union College annual / Jewish Institute of Religion, 1999)
Over the past century, the Mekhilta of Rabbi Shimon b.Yoḥai has been subject to disproportionately little scholarly consideration compared with its tannaitic counterparts. This is due primarily to sustained scholarly concern about the reliability of the text, which was reconstructed first by D. Hoffmann, and subsequently by J. N. Epstein and E.Z. Melamed, through highly complex processes from a large number of diverse sources. An analysis of these reconstructions reveals, however, that a common thread of editorial processes, guided by a common core of assumptions about early rabbinic textuality, binds together all the textual editions of the tannaitic midrashim. The question begs, therefore: why has the validity of the Mekhilta of Rabbi Shimon b. Yoḥai, in particular, come into question? The crux of the issue is the nature of the evidence available to Hoffmann and Epstein-Melamed for use in the construction of their editions of the text. A particular reason for skepticism is their reliance upon Midrash ha-Gadol as a source for textual material. However, a detailed examination and comparison of tractate Pisḥa in both editions of the Mekhilta of Rabbi Shimon b. Yoḥai reveals a high degree of correspondence between the various manuscript materials and Midrash ha-Gadol, and makes it possible to appraise more fully the overall reliability of the tractate in the Epstein-Melamed edition, and to a lesser extent, the reliability of the entire text.